The bookseller and binder Manuel Millana in the Royal Academy of Fine Arts of San Fernando - Flores Hernández, Yohana Yessica; Carpallo Bautista, Antonio; Moro Pajuelo, Marisa (Revista General de Información y Documentación, 2019)
The main objective of this article is to study the work done by the bookseller and binderManuel Millana in the Royal Academy of Fine Arts of San Fernando, between 1776 and 1810, at theRoyal Academy of Fine Arts of San Fernando, carried out by consulting the books of accounts andfiles of the Archive of the Academy and the on-site analysis of the bindings described in thedocumentation, thus knowing better the type of bindings ordered, their prices, materials, recipients,helping to better understand the history of the institution itself, the guild of booksellers, printers andbookbinders from Madrid and therefore of the Madrid society of the time.
Keywords: Modern Age; Madrid; Royal Academy of Fine Arts of San Fernando; Millana; Manuel; Booksellers-Bookbinders; Study and description; Historical Binding